Screening Methods of Antioxidant Activity: An Overview - Sharma, Ajay; Bhardwaj, Sudhir; Mann, A.S.; Jain, Amit; Kharya, M. D. (Pharmacognosy Reviews)
This study was intentional to assess the antioxidant activity of drugs. The antioxidants divulge an gigantic ability to trim down DPPH, superoxide, peroxide and nitric oxide radical scavenging activity. Antioxidants restrain OH─ radical induced oxidation of protein (BSA) and LPO in hepatic microsomes. The fortitude of metal chelating competence of antioxidant indicates chelation of metal ions (Fe2+) to be a putative means concerned in the inhibition of OH─ radical induced BSA oxidation and LPO. Antioxidants also exhibited a noteworthy activity in discriminating oxidative tissue grievance animal model constituted by CCl4 induced hepatotoxicity. The administration of the antioxidant significantly defend CCl4 induced elevation in AST and ALT in the serum, elevation in hepatic LPO, diminution of hepatic GSH and decrease in the activities of hepatic antioxidant enzymes: SOD, CAT and GPX. Antioxidant gives fortification against histopathological changes produced by CCl4 such as necrosis, fatty changes, ballooning degeneration, etc.
Keywords: Antioxidant; Free radicals; 2; 2-Diphenyl-1-picrylhydrazyl; Nitroblue tetrazolium